AL amyloidosis with elevated peripheral blood cell counts – A frequent association with liver involvement. A single-center retrospective study - Mateusz Ziarkiewicz; Justyna Szczygieł; Marta Legatowicz-Koprowska; Joanna Drozd-Sokołowska; Piotr Boguradzki; Krzysztof Jamroziak; Grzegorz Basak (Leukemia Research Reports)
Background: AL amyloidosis is a systemic protein misfolding disorder characterized by organ deposition of monoclonal immunoglobulin fragments, with insidious onset and progressive course. The plasma cell clone in the bone marrow is relatively small and typically does not impair hematopoiesis, in contrast to multiple myeloma. Herein we present a novel observation of increased thrombocyte, leukocyte and erythrocyte counts in a subset of AL amyloidosis patients. Material and Methods: We performed a retrospective analysis of medical records of all consecutive patients diagnosed with AL amyloidosis at the Medical University of Warsaw in years 2001–2022, which included clinical, pathological and laboratory data, as well as treatment protocols and outcomes. Results: Twenty-three patients out of 124 (18.4 %) included had elevated blood counts: 17 (13.6 %) had leukocytosis with neutrophilia, 7 (5.6 %) had thrombocytosis, whereas 2 (1.6 %) had erythrocytosis. In comparison to the remaining AL population this subgroup was characterized by younger age (median 57 vs 62 years, p = 0.018), higher frequency of hepatomegaly (42.9 % vs.14.7 %, p = 0.004), higher median alkaline phosphatase concentration (129 U/L vs 93 U/L, p = 0.006) and more frequent hepatic amyloidosis (34.8 % vs 10.3 %, p = 0.003). None of the patients had definite features of a myeloproliferative neoplasm, although genetic testing was available in 5 out of 9 cases with thrombocytosis or erythrocytosis. There were no significant differences in terms of survival between patients with elevated cell counts and non-polycythemic patients (median overall survival 2.9 vs 6.6 years, p = 0.51, median event-free survival 0.7 vs 1.8 years, p = 0.29, respectively). Conclusions: Elevated peripheral blood counts in a subset of patients with AL amyloidosis constitute a rare but significant phenomenon and appear to be associated with frequent hepatic involvement. We hypothesize that cytokine deregulation and hyposplenism may belong to its pathomechanisms.